Subjective and Objective Measurement of Sleep Quality and Activity in Glaucoma. Issue 4 (7th April 2023) - Stoner, Ari M.; Patnaik, Jennifer L.; Ertel, Monica K.; Capitena-Young, Cara E.; SooHoo, Jeffrey R.; Pantcheva, Mina B.; Kahook, Malik Y.; Seibold, Leonard K.
Abstract : Précis: Glaucoma patients exhibit worse indices of sleep function by both objective and subjective metrics compared with controls. Purpose: The purpose of this study is to characterize the sleep parameters and physical activity levels of glaucoma patients compared with controls. Patients and Methods: A total of 102 patients with a diagnosis of glaucoma in at least 1 eye and 31 control subjects were enrolled in the study. Participants completed the Pittsburgh Sleep Quality Index (PSQI) during enrollment and then wore wrist actigraphs for 7 consecutive days to characterize circadian rhythm, sleep quality, and physical activity. The primary outcomes of the study were subjective and objective metrics of sleep quality using the PSQI and actigraphy devices, respectively. The secondary outcome was physical activity, measured by the actigraphy device. Results: From the PSQI survey, glaucoma patients had higher (worse) scores compared with controls for sleep latency, sleep duration, and subjective sleep quality, whereas scores for sleep efficiency were lower (better), suggesting more time spent in bed asleep. By actigraphy, time in bed was significantly higher in glaucoma patients as was time awake after sleep onset. Interdaily stability, quantifying the synchronization to the 24-hour light-dark cycle, was lower in glaucoma patients. There were no other significant differences between glaucoma and control patients with regard to rest-activity rhythms or physical activity metrics. In contrast to the survey data, findings from the actigraphy demonstrated that there were no significant associations between the study group and controls regarding sleep efficiency, onset latency, or total sleep time. Conclusions: In this study, patients with glaucoma demonstrated several subjective and objective differences in sleep function when compared with controls, whereas physical activity metrics were similar.